Early T-cell precursor acute lymphoblastic leukemia: diagnostic pitfalls, genomic alteration, novel therapeutics, and minimal residual disease monitoring - George, Binsah; Chan, Kok Hoe; Rios, Adan (Frontiers in Hematology, 2024)
Early precursor T-cell acute lymphoblastic leukemia (ETP-ALL) is a rare type of T-cell ALL (T-ALL) that was initially described in 2009. Since its initial description, it has been formally recognized as a distinct entity, according to the 2016 World Health Organization classification. ETP-ALL is characterized by unique immunophenotypic and genomic profiles. The diagnosis and management of ETP-ALL remain challenging. Poorer outcomes, high incidence of induction failure and relapsed/refractory disease demand novel therapies. This review emphasizes the challenges of initial diagnosis, the molecular mechanisms underlying leukemogenesis, and the available therapeutic options. Additionally, it discusses the importance of induction failure, the prognostic value of detecting minimal residual disease, and the implications of hematopoietic stem cell transplantation, along with emerging novel therapies.